A comparative study of the quality of sewage waste waterof Diwaniyah textile mill and waste water treatment plant in Diwaniya - Foad M. Alkm, et.al (Al-Qadisiyah Journal of Pure Science, 2017)
The current study was conducted on two types of industrial wastewater of heavy water to a textile factory Diwaniyah S1 and S2 and municipal water treatment plant Diwaniya, S3 and S4 in the city of Diwaniyah _ Iraq. Confirmed this study on changes of spatial - temporal to some physical and chemical properties and algal content of these sites, the importance of this study stems from the importance of the Diwaniya River(Shatt al-Diwaniya), which receives large loads of pollutants from both sites under study (factory and processing plant). Monthly samples of water and algae werecollected for the duration of study (Spring 2011 - Spring 2012).The results of physical and chemical tests following temperature ranges (13.7-31.1 º C) pH (7.0-7.8), electrical conductivity (1225-2045 μS / cm) Total suspended solids TSS (58.5-277.2 mg / L) of dissolved oxygen (0.7-8.11 mg / l), biochemical oxygen requirement BOD (41.49-200.43 mg / l) nitrite NO2 (0.423-12.25 mg / L) of nitrate NO3 (161.85-637.57 mg / l) effective phosphate (81.3-1141 Mcgm / l)the total number of phytoplankton (17,000- 14202.75 individual / L) the spatial and temporalhave shown changes of high significant differences at (p ≤ 0.05) among the stations and seasons,the results showed qualitative study of algae that dominance was for blue green algae(cyanophyceae)by 46%, followed by algae Bacilliariophyceae (diatoms) by 27%, and finally algae dinophycesaeby 3%. On the other hand, according to data of Shannon – Wiener index (H) of the diversity of the fall and winter varieties on they were extremely pollution in all stations 0.377 and 0.669, respectively, while summer and spring, moderate pollution of class (П) values were manual Shannon - Weiner is 1,374According to the manual species richness, the first leg was the best, followed by the station fourth ,third and second came in last, but in terms of abundance, the third leg of the rest of the stations topped followed fourth ,second and finally the first. And as conclusion the current study showed that algal studies can give early warning and an accurate assessment about the quality of sewage before deliverd to the river.